Distribution of nano-, micro- and netplankton chlorophyll in the surface water of the Indian sector of the Southern Ocean, 1985/86 - Hattori, Hiroshi; Fukuchi, Mitsuo (National Institute of Polar Research, 1989)
P(論文) Size fractionation of phytoplankton stock in the surface water was studied in the Indian sector of the Southern Ocean. Bucket sampling from 0 m and pump sampling from 8 m depth were conducted for the surface water. A total of 75 pairs of samples were collected along the course of the icebreaker SHIRASE during the cruise of the 27th Japanese Antarctic Research Expedition (JARE-27) from December 1985 to March 1986 for observing geographical distribution of phytoplankton stock and for evaluating the effectiveness of the pump system. Chlorophyll a concentration in the surface water was high at the southern margin of the Subantarctic water (52-55°S) reaching more than 1.32 μgl^<-1> (December) and more than 0.59 μgl^<-1> (February to March). Chlorophyll a concentration in the Indian sector of the Antarctic water varied geographically; high in the eastern offing of Enderby Land and low in the western offing. The standing stock of nanoplankton (<5 μm) and microplankton (5-20 μm) was constant at 0.12±0.09 and 0.03±0.03 μgl^<-1>, respectively. Netplankton fraction (>20 μm) was higher than smaller fractions (0.18±0.28 μgl^<-1>). Regional variations of the total phytoplankton chlorophyll stock are mainly associated with variations in netplankton fraction stock. No significant difference of chlorophyll a concentration between the bucket-sampled water and the pumped-up water was detected by statistical analysis. This reveals that the pumped-up water is sufficient for chlorophyll analysis in the routine works of marine biological program of JARE. departmental bulletin paper